Back Cover: A velocity program using the Kanade–Lucas–Tomasi feature‐tracking algorithm with demonstration for pressure and electroosmosis conditions. Issue 7 (17th April 2022) - Devasagayam, Jasen; Bosma, Rick; Collier, Christopher M.
Abstract : DOI: 10.1002/elps.202100177 The cover picture shows the microparticles which were tracked using the KLT feature‐tracking algorithm under pressure‐driven and electroosmosis conditions. The top of the image features the T8050 glass microfluidic chip which the tests were performed on. The insets at the T‐intersection of the microfluidic chip demonstrates a series of silica microfluidic particles flowing through the buffer solution of the microfluidic chip. In this study, these microparticles were tracked, and the resulting velocity profiles were computed, to demonstrate the effectiveness of the KLT feature‐tracking algorithm.